NATIONAL HEALTH INSURANCE CONTRIBUTION COMPLIANCE STRATEGY FOR EMPLOYERS: PROTECTION AND LEGAL RISKS - Lili Riyanti As; Andi Muhammad Asrun; Iwan Darmawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The development of the National Health Insurance (JKN) policy in Indonesia has created dynamics in the efforts to enforce compliance with contributions by employers. On one hand, the strengthening of regulations provides clearer protection for workers thru guarantyd participation and the sustainability of access to health services. On the other hand, the implementation of administrative sanctions and increasingly stringent enforcement mechanisms pose challenges for employers in fulfilling these obligations. This study aims to analyze the implementation of the intersectoral enforcement model in JKN contribution compliance and its implications for worker protection and legal risks for employers. The method used is a normative juridical approach with an analysis of the relevant legislation. The research results show that the intersectoral model can enhance the effectiveness of law enforcement thru data integration and inter-agency coordination. However, there are still obstacles such as data inconsistencies between agencies and limited supervisory capacity. The implication of implementing this model is the increased transparency and accountability in the JKN system, while also providing more optimal protection for workers without neglecting legal certainty and business continuity for employers.